Investigation of light crude oil removal using biocoal from torrefaction of biomass waste - ÖZVEREN, UĞUR (My University, 2022)
Oil spills pose a significant threat to aquatic life worldwide. However, cleaning up oil spills can be difficult and expensive. Therefore, research on efficient and environmentally friendly methods to treat oil spills is an important issue. In this study, biocoal obtained from torrefaction of cypress cone waste at 300 ◦C was used to investigate the efficient and environmentally friendly methods for treating oil spills. In addition, RAMAN, XRD, SEM and FT-IR were used to study the morphology and structure of the biocoal-based adsorbent. Structural and morphological analyzes show that the torrefied cypress cone has a porous and heterogeneous surface, which is advantageous for adsorption of oil contaminants from seawater. The adsorption process was also evaluated by kinetic analysis. The results showed that cypress cone-based biocoal can be used as a promising adsorbent for the treatment of oil spills with a good adsorption capacity of 6.587 g/g within 120 min.
Keywords: Torrefaction; Biocoal; Cypress cone waste; Oil spill; Adsorption; Remediation